PROTOTIPE TERMOMETER BERBASIS TERMOELEKTRIK UNTUK PEMBELAJARAN FISIKA MATERI SUHU DAN KALOR - Sugeng Riyadi; Eko Suyanto; Ismu Wahyudi (Jurnal Pembelajaran Fisika, 2015)
The purpose of this research development was to elaborate thermometer based on thermoelectric along with the user manual for physics learning of temperature and heat topics. The steps of thermoelectric thermometer development used development prosedure based on Suyanto, consited of stages of needs analysis, identification of sources power, identification of product specifications, product development, product testing, and the final production in prototype form. Based on the test results that have been done, it is known that thermoelectric thermometer has specifications; 2.20% precision, stray 0.48, sensitivity of 0.62 C / mV, and a measuring range of 25C-95C. The results of the feasibility test of thermoelectric thermometer and user manual showed that the product is proper to use as an alternative temperature measuring device with a score of 3.8 on the physical eligibility test and a score of 3.3 on the test design experts.Tujuan dari penelitian pengembangan ini adalah mengembangkan termometer berbasis termoelektrik beserta petunjuk penggunaan untuk pembelajaran fisika materi suhu dan kalor. Tahapan pengembangan termometer termoelektrik beserta petunjuk penggunaannya menggunakan prosedur pengembangan menurut Suyanto, meliputi analisis kebutuhan, identifikasi sumber daya, identifikasi spesifikasi produk, pengembangan produk, uji produk, dan produksi akhir dalam bentuk prototipe. Berdasarkan hasil uji yang telah dilakukan, diketahui spesifikasi termometer termoeletrik yaitu; ketelitian alat 2,20 %, sesatan 0,48, sensitivitas 0,62 C/mV, dan rentang ukur 25C-95C. Hasil uji kelayakan termometer termoelektrik dan petunjuk penggunaan menyatakan bahwa produk layak untuk digunakan sebagai termometer alternatif dengan skor 3,8 pada uji kelayakan fisik dan skor 3,3 pada uji ahli desain.Kata kunci: pengembangan, termoelektrik, termometer